Pengendalian Bahan Baku Produk Jamu Sinom dengan Metode Material Requirement Planning untuk Meminimasi Biaya Produksi Di UD. Sanfaat. - Mustaqim; Bagus Adi Permana; Ratna Diah Yuniawati (Ekliptika, 2026)
Sanfat is a company that produces Jamu Sinom drinks from traditional ingredients. This company often experiences difficulties in obtaining turmeric as the raw material. If this happens, it will certainly increase the production costs of Jamu Sinom. Therefore, it is necessary to control raw materials using the Material Requirement Planning (MRP) and Moving Average Forecast methods to determine future raw material needs. During this period, the company purchased an average of 75.0 kg. The ordering cost was Rp. 160,000 and the storage cost was Rp. 500,000. The total cost of raw material inventory in 1 year was Rp. 11,600,000. Based on calculations and analyses carried out using the Material Requirement Planning (MRP) method with lot-for-lot and Economic Order Quantity (EOQ) lot-for-lot calculations resulted in a total cost of Rp. 17,820,000 and the EOQ calculation resulted in a total cost of Rp. 8,140,000. The minimum raw material order is EOQ, which can be used as a raw material control solution for Sinom herbal products at UD. Sanfaat.